2016
DOI: 10.1097/prs.0000000000002456
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery Workout: A Novel Simulation Training Curriculum Based on Nonliving Models

Abstract: Significant acquisition of microsurgical skills was achieved by trainees to a level similar to that of experienced surgeons. Acquired skills were transferred to a more complex live model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Each participant was given a desktop microscope (45X zoom, 10 cm working distance, www.worldmicrotraining.com), microsurgical instruments (micro-needle holder, microscissors, microsurgical forceps, vessel dilator), 3 ml syringe filled with water for injection and an 8.0 ethilon TM suture to complete their task. A pre-dissected non-living, chicken thigh femoral vessel model was used for the purpose of our study (24). The vessel was mounted on a display pad, free of tension and an arteriotomy performed in the center of the vessel.…”
Section: Methodsmentioning
confidence: 99%
“…Each participant was given a desktop microscope (45X zoom, 10 cm working distance, www.worldmicrotraining.com), microsurgical instruments (micro-needle holder, microscissors, microsurgical forceps, vessel dilator), 3 ml syringe filled with water for injection and an 8.0 ethilon TM suture to complete their task. A pre-dissected non-living, chicken thigh femoral vessel model was used for the purpose of our study (24). The vessel was mounted on a display pad, free of tension and an arteriotomy performed in the center of the vessel.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the principal advantage of the model using latex balloons is the possibility of using it to teach several different vascular suture techniques, in contrast to what is described in the majority of studies in the literature, which only tested end-to-end anastomosis. 2,3,6,19,20 Some studies used mononylon sutures to perform anastomoses. 6,19,20 In our model, anastomoses were constructed using fine polypropylene sutures and two needles, to make the model more realistic and help familiarize the students with the vascular technique.…”
Section: Discussionmentioning
confidence: 99%
“…There are descriptions in the literature of using synthetic materials, such as silicone and rubber gloves, animal tissues, and vegetable tissues, and of gaining practical experience using small animals (pigs, rats, and rabbits), as part of teaching of vascular anastomosis and development of the skills needed. [1][2][3][4][5] However, use of animal models is the most common objection raised by the public and by the students themselves, who question the practice of sacrificing animals for educational purposes. 6 The strict rules mandated by the Institutional Committees on Care and Utilization of Animals also make using such animal models in medical training difficult, contributing to the need to develop alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The first cohort of residents received a conventional microsurgery training at our Simulation Center Laboratory which has been previously validated and is a part of our residency program curriculum. 22 This was the control group and was called the “MicroLab group.” Their training was performed in 17 practice sessions of progressive difficulty, with six of them focusing on performing complete end-to-end arterial anastomosis on a 1-mm chicken wing. They were tutored in all the training sessions by an expert in our laboratory.…”
Section: Methodsmentioning
confidence: 99%